Guidelines for Developing Secondary Cities into Tourist Attractions Worth Visiting for Senior Tourists with Spending Potential - Kaewudom, Yongyut; jaiuea, monrat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
This research aims to study the tourist behavior of senior tourists in secondary cities, assess the potential of these cities as attractive destinations, evaluate word-of-mouth and the likelihood of repeat visits, and propose guidelines for developing secondary cities into attractive destinations for senior tourists with high spending potential. This study employs a mixed-methods approach. Quantitative data was collected from 400 high-spending Thai senior tourists through multi-stage sampling. Initially, a quota of 100 respondents was selected from each of four provinces across four regions, followed by purposive sampling. Data was gathered through a questionnaire and analyzed using descriptive statistics and stepwise multiple regression. For the qualitative part, data was collected from 12 stakeholders involved in promoting and developing secondary city tourism, using purposive sampling, small group discussions, and content analysis. The findings reveal that high-spending senior tourists typically travel twice a year during extended holidays, averaging three days per trip, primarily for leisure. They gather information mainly from social media, with children or relatives serving as the primary decision-makers. These tourists travel with family, plan their trips independently, use personal vehicles, prefer destinations outside their region, favor natural attractions, stay in hotels, and spend between 10,001 and 15,000 Baht per trip, with food and beverages being the main expenses. The potential evaluation of secondary cities indicates a high level of appeal, and these senior tourists demonstrate strong word-of-mouth promotion and a high intention to revisit. The factors that influence the word-of-mouth and revisit intentions of senior tourists include attractions, accommodations, activities, and amenities. The proposed development guidelines for transforming secondary cities into attractive tourist destinations for senior tourists are: 1) developing attractions, 2) upgrading accommodation standards, 3) designing tailored tourism activities, and 4) improving tourism amenities.